2018
DOI: 10.1136/thoraxjnl-2018-212096
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of viruses and bacteria to community-acquired pneumonia in vaccinated children: a casecontrol study

Abstract: IntroductionRespiratory pathogens associated with childhood pneumonia are often detected in the upper respiratory tract of healthy children, making their contribution to pneumonia difficult to determine. We aimed to determine the contribution of common pathogens to pneumonia adjusting for rates of asymptomatic detection to inform future diagnosis, treatment and preventive strategies.MethodsA case–control study was conducted among children <18 years in Perth, Western Australia. Cases were children hospitalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 47 publications
5
59
1
5
Order By: Relevance
“…Human rhinovirus (RV), bocavirus, adenovirus, coronavirus, polymavirus, and Anneloviridae family viruses have been identified in the URT of large proportions of healthy asymptomatic children using PCR-based methods and metagenomics, even in geographically isolated locations (van den Bergh et al, 2012;Bogaert et al, 2011;Wylie et al, 2012;Altan et al, 2019). Detection frequency of these viruses in many studies is not different in the URT of asymptomatic controls and children hospitalized due to the respiratory tract infections, in contrast to respiratory syncytial virus (RSV), human metapneumovirus (hMPV), parainfluenza viruses (PIVs), and influenza, being causally associated with hospitalizations, lower respiratory symptoms, and pneumonia (Singleton et al, 2010;Sarna et al, 2018;Bhuiyan et al, 2019). These data suggest that in the cases of these ''commonly carried'' URT viruses, not only their presence, but rather total viral load (Jansen et al, 2011) or complex interactions between viruses and bacteria (van den Bergh et al, 2012) or other environmental (e.g., allergen) and intrinsic host factors (e.g., sensitization) (Rubner et al, 2017) determine the occurrence of disease in the URT or LRT.…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…Human rhinovirus (RV), bocavirus, adenovirus, coronavirus, polymavirus, and Anneloviridae family viruses have been identified in the URT of large proportions of healthy asymptomatic children using PCR-based methods and metagenomics, even in geographically isolated locations (van den Bergh et al, 2012;Bogaert et al, 2011;Wylie et al, 2012;Altan et al, 2019). Detection frequency of these viruses in many studies is not different in the URT of asymptomatic controls and children hospitalized due to the respiratory tract infections, in contrast to respiratory syncytial virus (RSV), human metapneumovirus (hMPV), parainfluenza viruses (PIVs), and influenza, being causally associated with hospitalizations, lower respiratory symptoms, and pneumonia (Singleton et al, 2010;Sarna et al, 2018;Bhuiyan et al, 2019). These data suggest that in the cases of these ''commonly carried'' URT viruses, not only their presence, but rather total viral load (Jansen et al, 2011) or complex interactions between viruses and bacteria (van den Bergh et al, 2012) or other environmental (e.g., allergen) and intrinsic host factors (e.g., sensitization) (Rubner et al, 2017) determine the occurrence of disease in the URT or LRT.…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…12 Em um estudo australiano feito em 230 crianças (< 18 anos) hospitalizadas com PAC e 230 controles saudáveis, entre 2015 e 2017, os vírus respiratórios, particularmente o VSR e o HMPV, foram os principais contribuidores para a etiologia da PAC. 13 Os autores estimaram que os vírus VSR, HMPV, influenza, adenovírus e Mycoplasma pneumoniae foram responsáveis por 20,2% (IC95%: 14,6 a 25,5), 9,8% (5,6% a 13,7%), 6,2% (2,5% a 9,7%), 4% (1,1% a 7,1%) e 7,2% (3,5% a 10,8%) das hospitalizações, respectivamente. 13 Por outro lado, em um estudo (Gabriel) multicêntrico feito em oito países em desenvolvimento ( 3).…”
Section: Etiologiaunclassified
“…13 Os autores estimaram que os vírus VSR, HMPV, influenza, adenovírus e Mycoplasma pneumoniae foram responsáveis por 20,2% (IC95%: 14,6 a 25,5), 9,8% (5,6% a 13,7%), 6,2% (2,5% a 9,7%), 4% (1,1% a 7,1%) e 7,2% (3,5% a 10,8%) das hospitalizações, respectivamente. 13 Por outro lado, em um estudo (Gabriel) multicêntrico feito em oito países em desenvolvimento ( 3). O VSR apresentou a maior fração etiológica (31,1%, IC95%: 28,4-34,2) de todos os patógenos.…”
Section: Etiologiaunclassified
“…This is important for the prophylaxis and management of CAP. Several case‐control studies have reported a higher risk of developing severe or very severe CAP (SCAP) among patients infected with RSV 4,5 . However, similar results have not been observed among Chinese children in Beijing, 3 suggesting that sustained effort is needed to understand whether viral infections lead to more serious disease.…”
Section: Introductionmentioning
confidence: 98%